Geant4-DNA simulation of radiation effects in DNA on strand breaks from ultra-low-energy particles - P. Nimmanpipug (2020)
© 2020 Elsevier B.V. The work was aimed at using Geant4-DNA software to simulate ultra-low-energy particle irradiation of DNA to understand relevant effects and fundamentals on DNA strand breaks. Light particle species of electron, hydrogen, proton, helium (He), He+ and He2+ with energy ranged in 10 – 1000 eV and fluence varied from 5 × 103 to 1 × 105 particles/cm2 irradiated DNA models, poly-AT, poly-CG and pGFP. The irradiation effect on DNA single strand breaks (SSBs) and double strand breaks (DSBs), particularly the latter, was focused. Results showed that the ratios between the numbers of SSBs and DSBs were nearly the same, independent of the particle energy and fluence. DSBs increased with increasing of ion energy, but not depended on the fluence. Discrepancies between the simulation and experiments were discussed, attributed to the simulation code overlooking the direct interaction of elastic collision between the particle and the DNA atom to cause atomic displacement.